Theos and polis political theology as discernment - Erp, Stephan van 1966-; Haers, Jacques 1956- (Peeters, 2023)
"This volume is the fruit of the twelfth LEST-conference (Leuven Encounters in Systematic Theology), which took place between 23 and 26 October 2019. The theme was "Theos & Polis: Political Theology as Discernment". Current global challenges – climate change, extreme poverty, large refugee camps, violence and abuse, failing democracies and the rise of populism – were the starting point for choosing this conference theme. The choice of the theme was also influenced by the theo-political concerns of people in churches worldwide and of a new generation of junior scholars and students in theology: How to theologically understand and respond to political situations that affect faith communities? How to shape a theology that both responds to local, socio-economic contexts and acknowledges being part of a global movement? How to engage with the politics of synodality as a new task for church and theology today? Part One (Understanding Political Theology as Discernment) could be seen as providing the theological and theoretical foundations for seeing, judging, and acting theo-politically. In Part Two (Discerning Political Theology in the Face of Trauma and Conflict), political theology is discerned in concrete situations. Part Three (Conversing with Political Theologians) presents ongoing discussions with modern philosophers and theologians who have impacted the development of political theology until today."
Includes index
Keywords: Geschichte; Politische Theologie; Konferenzschrift -- 2019 -- Löwen